Uji Aktivitas Senyawa Antibakteri Ekstrak Aloe Vera (Aloe Vera) Terhadap Infeksi Bakteri Edwardsiella Tarda secara In Vitro - Nuranti Anarkhis; Arief Prajitno; Maftuch Maftuch; Karimah Karimah (Postgraduate, University of Mataram, 2023)
Edwardsiella tarda is a type of gram-negative intracellular pathogen that can cause mass demise in fish farming. The development of edwarsiellosis due to E.tarda infection causes significant economic losses for cultivators. Aloe vera is a perennial succulent plant like a cactus, drought withstand, and belongs to the Liliaceae family, of which there are more than 360 known species (Wijaya and Masfufatun, 2022). Aloe vera is one of the plants known to contain active ingredients that can inhibit the growth of bacteria. The results of phytochemical analysis of a crude extract of Aloe vera showed the presence of active compounds, specifically flavonoids, tannins, triterpenoids, and saponins. MIC analysis showed that the lowest absorbance value of Aloe vera was obtained at a concentration of 50 mg/L with a value of 0.316, indicating a decrease at each concentration. The concentration of 50 mg/L is close to the positive control which indicates that at a concentration of 50 mg/L, it can be the reference for the lowest concentration in determining the dose of Aloe vera extract which is known that the presence of antibacterial compounds in Aloe vera extract can inhibit the growth of E.tarda bacteria. The inhibition zone test was carried out with graded concentrations of 50 mg/L, 100 mg/L, 150 mg/L, 200 mg/L and 250 mg/L with an observation time of 24 hours post-incubation and 48 hours post-incubation. Inhibition zone analysis with the highest diameter was at 200 mg/L. SEM analysis by distributing a crude extract of Aloe vera affected E.tarda bacteria specifically, lysis occurring in bacterial cells